Promoting Success and Persistence in Pandemic Times: An Experience With First-Year Students - Casanova, Joana R.; Gomes, Alexandra; Moreira, Maria Alfredo; Almeida, Leandro S. (Frontiers in Psychology, 2022)
The transition and adaptation of students to higher education involves a wide range of challenges that justify some institutional practices promoting skills that enable students to increase their autonomy and to face the difficulties experienced. The requirements for this adaptation were particularly aggravated by the containment and sanitary conditions associated with COVID-19. With the aim of promoting academic success and preventing dropout in the first year, a support program was implemented for students enrolled in two courses in the area of Education at a public university in northern Portugal during the first semester of 2020/2021. Three sessions of 50/60 minutes were implemented: the 1st session focused on the verbalization of the demands, challenges and difficulties of the transition; the 2nd and 3rd sessions focused on the difficulties of academic adaptation and academic performance. Data from a dropout risk screening instrument and from the activities performed during sessions were analyzed. The main results point to student satisfaction with the content and the activities of the sessions and their usefulness. Students also report high satisfaction levels with higher education attendance, but some emotional exhaustion due to academic activities. The continuity of the program is recommended with some improvements in its planning in order to ensure a more definitive version of the program in the next two years.